1H-MRS glutamate level predicts auditory sensory gating in alcohol dependence: Preliminary results. Issue 1 (December 2015) - Thoma, Robert; Long, Jason; Monnig, Mollie; Yeo, Ronald; Petropoulos, Helen; Gasparovic, Charles; Pommy, Jessica; Mullins, Paul
Abstract Background Impairment in auditory sensory gating (ASG) has been documented in alcohol dependence [1]. Likewise, it has been shown that ASG becomes abnormal during alcohol administration in otherwise healthy individuals [2]. Patterns of gating abnormality associated with alcohol use are likely associated with an alcohol responsive neurochemical like glutamate (Glu), particularly since it is well-established that alcohol affects NMDA receptors and that glutamatergic functioning is abnormal in both acute alcohol use and in alcohol dependence [3]. Hence, a link between Glu metabolite levels and ASG was hypothesized. It was first hypothesized that Glu and ASG abnormality would be found in groups with alcohol dependence. A second hypothesis was that across groups, greater Glu would predict reduced ASG. Methods Groups were comprised of healthy, non-drinking controls (Controls, N  = 4), individuals with current alcohol dependence (AUD-current, N  = 6), and with alcohol dependence in remission for at least 1 year (AUD-remission, N  = 6). Participants underwent a diagnostic assessment for alcohol consumption, MRI, 1H-MRS for in vivo assessment of Glu and other metabolites, and MEG scanning during a paired click protocol. ASG was computed as the ratio of the source strength of the 50 ms component in the event related field (ERF) to the second click in the pair divided by the source strength of the 50 ms component to the first click in the pair. Results Univariate MANOVAs controlling for age and gender revealed a significant effect for group on Glu and ASG, such that ASG ratios were significantly elevated, implying weakened gating. Glu concentration was reduced in AUD-current relative to the other two groups. Further analysis revealed that when additionally controlling for the group effect, reduced Glu predicted increasing impairment in ASG. Conclusions The overall results were consistent with the hypothesis that differences in Glu metabolite levels associated with alcohol dependence result in impaired ASG.